Climate Change and Economic Policy in Pakistan: A Roadmap for Sustainable Development - Rameez Haider,; Afaq Ahmad Chughtai,; Rabail Ali Kahan, (Dialogue Social Science Review (DSSR), 2025)
Climate change poses a profound threat to Pakistan’s economic stability, agricultural productivity, water resources, and public health. As one of the most climate-vulnerable countries in the world, Pakistan faces the dual challenge of mitigating environmental risks while pursuing economic growth. This paper explores the intricate relationship between climate change and economic policy in Pakistan, proposing a roadmap for sustainable development that aligns environmental resilience with economic planning. It examines existing policy frameworks, identifies key gaps in implementation, and analyzes the potential of green economy strategies, climate-smart agriculture, and renewable energy investments. Through policy integration and institutional reform, the paper argues that Pakistan can transition towards a low-carbon, climate-resilient economy. The study concludes with actionable recommendations aimed at fostering sustainable development, reducing vulnerability, and ensuring long-term economic and environmental security. Keywords: Pakistan, Climate Change, Economic Policy, Sustainable Development